Impaired IGF1R signaling in cells expressing longevity-associated human IGF1R alleles - Cagdas Tazearslan; Jing Huang; Nir Barzilai; Yousin Suh (2011)
Dampening of insulin/insulin-like growth factor-1 (IGF1) signaling results in the extension of lifespan in invertebrate as well as murine models. The impact of this evolutionarily conserved pathway on the modulation of human lifespan remains unclear. We previously identified two IGF1R mutations (Ala-37-Thr and Arg-407-His) that are enriched in Ashkenazi Jewish centenarians as compared to younger controls and are associated with the reduced activity of the IGF1 receptor as measured in immortalized lymphocytes. To determine whether these human longevity-associated IGF1R mutations affect IGF1 signaling, we engineered mouse embryonic fibroblasts (MEFs) expressing the different human IGF1R variants in a mouse Igf1r null background. The results indicate that MEFs expressing the human longevity-associated IGF1R mutations attenuated IGF1 signaling, as demonstrated by significant reduction in phosphorylation of both IGF1R and AKT after IGF1 treatment, in comparison with MEFs expressing the wild-type IGF1R. The impaired IGF1 signaling caused by the IGF1R mutations resulted in the reduced induction of the major IGF1-activated genes in MEFs, including EGR1, mCSF, IL3Rα, and TDAG51. Furthermore, the IGF1R mutations caused a delay in cell cycle progression after IGF1 treatment, indicating a dysfunctional physiological response to a cell proliferation signal. These results demonstrate that the human longevity-associated IGF1R variants are reduced-function mutations, implying that dampening of IGF1 signaling may be a longevity mechanism in humans.